Integration and Comparative Analysis of Remote Sensing and In Situ Observations of Aerosol Optical Characteristics Beneath Clouds - Jing Chen; Jing Duan; Ling Yang; Yong Chen; Lijun Guo; Juan Cai (Remote Sensing)
Lidar is the primary tool used to determine the vertical distribution of aerosol optical characteristics. Based on the observation characteristics of the mountain’s gradient, a validation analysis of the remote sensing and in situ observations of the aerosol optical characteristics and research on seasonal, monthly, and daily variations in aerosol optical depth (AOD) were performed using the dual-wavelength Lidar deployed at the foot of Mt. Lu and the aerosol particle-size spectrometer at the top of Mt. Lu. The validation results show that at the comparison heights, under cloudy-sky conditions with strong winds (>3.4 m/s) and high relative humidity (RH) (>70%), the aerosol extinction coefficients between the two sites are in good agreement; thus, the observations at the top of the mountain are more suitable for in situ validation under cloudy-sky conditions; however, the local circulations under clear-sky conditions lead to large differences in the aerosol properties at the same altitude between the two sites and are unsuitable for validation. An analysis of the AOD data from Mt. Lu reveals the following: (1) The AOD seasonal distribution frequencies under both clear-sky and cloudy-sky conditions are unimodal, with a values of 0.2∼0.6, and the inhomogeneity of the aerosol distribution in winter is evident; the seasonal difference in the AOD under clear-sky conditions is more significant, following the order of spring > summer > winter > autumn, and the AOD seasonal difference under cloudy-sky conditions is not obvious. (2) In the analysis of the AOD monthly variations, due to the influence of the meteorological conditions (high humidity, low wind speed) and pollutant transport, the AOD reached its peak in February (clear-sky: 0.63, cloudy-sky: 0.82). (3) Under clear-sky conditions, the negative correlation between the daily variations in AOD, and visibility is more significant during the daytime, and after 12:00, the AOD is positively correlated with <semantics>PM2.5</semantics>; these results indicate that the AOD is affected mainly by pollutants and the boundary layer height. Under cloudy-sky conditions, the peaks in the daytime AOD are related to the morning and evening rush hours, the correlations with the visibility and <semantics>PM2.5</semantics> are low, and the accumulation of pollutants during the nighttime. And (4) overall, the AOD is greater under cloudy-sky conditions than under clear-sky conditions; this result is likely related to the more favorable subcloud humidity conditions for aerosol hygroscopic growth.